Implementation of Village Staff Recruitment and Selection in Sidoarjo Regency - Eri Mega Selvia; Isnaini Rodiyah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2020)
This study aims to analyze and describe the implementation of recruitment and selection of village officials in Sidoarjo Regency as well as supporting and inhibiting factors for the implementation of recruitment and selection of village officials in Sidoarjo Regency. The research method uses descriptive research with a qualitative approach. Data collection is done by observation, interviews, and documentation with informants. Data analysis techniques using the theory of Miles & Huberman, namely data collection, data reduction, data presentation, and conclusions. The results showed that the implementation of the recruitment and selection of village officials in Sidoarjo Regency had been carried out in accordance with regulations where the registration and selection process was carried out in each village and the online selection process using a computer. The formation of the recruitment and selection committee for the village apparatus was carried out through a meeting led by the Village Head, but the condition of the facilities and infrastructure in the recruitment and selection of the village apparatus in the village was inadequate because participants were required to bring their own laptops. Communication has been carried out well by the parties, namely through socialization. Supporting factors and obstacles to the implementation of recruitment and selection of village officials in Sidoarjo Regency, namely supporting factors consisting of SOPs have been implemented well. While the inhibiting factor is the implementation of the online selection of village equipment in Desa Kepambat having a schedule delay due to a server error. In addition, the facilities and infrastructure in Tulangan District are inadequate